Identification Of Plasma Serotonin And Adiponectin As Predictor Biomarkers For Early Detection Of Breast Cancer Among Karbala Province - Almaialy, Zahraa Abduladheem; Hussein, Muna Ali; Mezher, Z. Abdul Alamir (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
Breast Malignancy Is The Most Common Malignancy Among Women, Constituting Eighteen Percent Of All Cancer Diagnoses In Females. It Is The Seventh Leading Cause Of Cancer-Related Fatalities Worldwide. The Goal Of This Research Is To Find Out How Breast Cancer Patients And Healthy People’s Levels Of The Hormones Serotonin (St) And Adiponectin (Adp) Compare. A Group Of 85 People With Breast Cancer And 85 People Who Appeared To Be In Good Health Had Their Serum Concentrations Of The Hormones Serotonin (St) And Adiponectin (Adp) Measured. When Compared To The Control Group, Breast Cancer Patients’ Serum Levels Of The Hormones Serotonin (St) And Adiponectin (Adp) Were Significantly Lower (P ≤ 0.05). In Comparison To Healthy Controls, Breast Cancer Patients Have Substantially Reduced Levels Of The Hormones Serotonin (St) And Adiponectin (Adp).